Hypoxia gradually augments metabolic and thermoperceptual responsiveness to repeated whole‐body cold stress in humans - Keramidas, Michail E. (Exp Physiol, 2020)
NEW FINDINGS: What is the central question of this study? In male lowlanders, does hypoxia modulate thermoregulatory effector responses during repeated whole‐body cold stress encountered in a single day? What is the main finding and its importance? A ∼10 h sustained exposure to hypoxia appears to mediate a gradual upregulation of endogenous heat production, preventing the progressive hypothermic response prompted by serial cold stimuli. Also, hypoxia progressively degrades mood, and compounds the perceived thermal discomfort, and sensations of fatigue and coldness. ABSTRACT: We examined whether hypoxia would modulate thermoeffector responses during repeated cold stress encountered in a single day. Eleven men completed two ∼10 h sessions, while breathing, in normobaria, either normoxia or hypoxia ([Formula: see text]: 12 kPa). During each session, subjects underwent sequentially three 120 min immersions to the chest in 20°C water (CWI), interspersed by 120 min rewarming. In normoxia, the final drop in rectal temperature (T (rec)) was greater in the third (∼1.2°C) than in the first and second (∼0.9°C) CWIs (P < 0.05). The first hypoxic CWI augmented the T (rec) fall (∼1.2°C; P = 0.002), but the drop in T (rec) did not vary between the three hypoxic CWIs (P = 0.99). In normoxia, the metabolic heat production ([Formula: see text]) was greater during the first half of the third CWI than during the corresponding part of the first CWI (P = 0.02); yet the difference was blunted during the second half of the CWIs (P = 0.89). In hypoxia, by contrast, the increase in [Formula: see text] was augmented by ∼25% throughout the third CWI (P < 0.01). Regardless of the breathing condition, the cold‐induced elevation in mean arterial pressure was blunted in the second and third CWI (P < 0.05). Hypoxia aggravated the sensation of coldness (P = 0.05) and thermal discomfort (P = 0.04) during the second half of the third CWI. The present findings therefore demonstrate that prolonged hypoxia mediates, in a gradual manner, metabolic and thermoperceptual sensitization to repeated cold stress.